Keepers Of Light : History and Speculations on the Future of Icelandic Lighthouses - Pradhan, Vikram, 1997- (2020)
The Icelandic word for a lighthouse is viti, which means "to know," and know where one is sailing. Lighthouses are relics of a bygone age and engineering marvels that have stood the test of time. Structures such as the lighthouse enable us to see and understand the passing of history and participate in time cycles that surpass individual life. These structures are instruments and museums of time. Out of the 22,100 lighthouses worldwide, only a few are still operational and manned by a lighthouse keeper. The last lighthouse keeper in Iceland was given notice around 2010 when Sigurdur Pálsson at Baugsstadir told a local newspaper that new technology in ships and lighthouses has made lighthouse keepers redundant. Some lighthouses today serve as tourist attractions and hotels and lose their significance and meaning. In this paper, we will discuss the history, present, and future of lighthouses in Iceland and worldwide. We will also look at the possibility of using the fields of design to create speculations on its future use.